â€œKNOWLEDGE MANAGEMENTâ€ PADA KELOMPOK TANI KARYA BERSAMA, DI DESA TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT, KABUPATEN MINAHASA - Raldy H. Assa; Leonardus Ricky Rengkung; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2017)
The purpose of this paper is to know the Knowledge Management of â€œKarya Bersamaâ€ farmers group at Tombasian Atas Village, Kawangkoan West, Minahasa District. This research was conducted from April to July 2016. The data used in this research are primary and secondary data. The variables measured were knowledge identification, knowledge creation, knowledge presentation and knowledge distribution. The analysis used is descriptive qualitative analysis by using content analysis. The results showed that the identification of group knowledge through cultivation, mass media, experience, TV media, newspapers and books, the presence of extension workers and among group members. Knowledge creation occurs through regular meetings among farmer groups. Knowledge presentation is carried out by exploiting technology utilization, demonstrating farming tools and distributing the knowledge gained.*lrr*